An Overview of MnAl Permanent Magnets with a Study on Their Potential in Electrical Machines - Sofia Kontos; Anar Ibrayeva; Jennifer Leijon; Gustav Mörée; Anna E. Frost; Linus Schönström; Klas Gunnarsson; Peter Svedlindh; Mats Leijon; Sandra Eriksson (Energies, 2020)
In this paper, hard magnetic materials for future use in electrical machines are discussed. Commercialized permanent magnets used today are presented and new magnets are reviewed shortly. Specifically, the magnetic MnAl compound is investigated as a potential material for future generator designs. Experimental results of synthesized MnAl, carbon-doped MnAl and calculated values for MnAl are compared regarding their energy products. The results show that the experimental energy products are far from the theoretically calculated values with ideal conditions due to microstructure-related reasons. The performance of MnAl in a future permanent magnet (PM) generator is investigated with COMSOL, assuming ideal conditions. Simplifications, such as using an ideal hysteresis loop based on measured and calculated saturation magnetization values were done for the COMSOL simulation. The results are compared to those for a ferrite magnet and an NdFeB magnet. For an ideal MnAl hysteresis loop, it would be possible to replace ferrite with MnAl, with a reduced weight compared to ferrite. In conclusion, future work for simulations with assumptions and results closer to reality is suggested.